Hub characteristics extraction of human proteins using tumor protein P53 – A case study - and N. Jiji2, T. Mahalakshmi1, M Sajeev2, N. Nijil Raj (Recent Research in Science and Technology, 2011)
This paper addresses the characteristic extraction of hub protein based on Tumor Protein P53 whose properties are already established and known to have key functionalities. These characteristics can throw some light in the direction of hub classification in a cost effective manner. Current methods in this line use Gene Ontology database or sequence homology which are time consuming and complex. The proposed method uses a 420 element vector for the characteristic filtering of hub character from HPRD database and has shown some positive results.